Pedagogia jesuíta para educação dos nativos na América Portuguesa no século XVI: Nóbrega e Anchieta - Melo, Jéssica Cristine De (2017)
This Master thesis consists in the study of the Jesuit pedagogy implemented in the mission on Brazilian lands, with emphasis on the non-institutional pedagogical strategies adopted to the formation of the Gentile as a Christian and subject of the Portuguese Crown. The methodology used for the research consisted in the analysis of some Jesuit letters, especially those from Manuel da Nóbrega and José de Anchieta, and also of the reading of other documents produced in the context of the sixteenth century. Besides that, the Master thesis counted on the contribution of contemporary scholars who deal with the issue of Jesuit pedagogy. One can conclude that the Jesuits, by means of an own Rationality, used pedagogical strategies for the conversion and education of the Gentiles in various places of Missionary. These strategies were even challenged by religious authorities of the Catholic Church and by the Society of Jesus itself. However, despite of beeing contested, the justification for using theses practices was based on the need to confront the reality of the forests of Portuguese America to accomplish the mission: the conversion of the Indians ad maiorem Dei gloriam.